The impact of financial literacy on the long term financial well being of students in the University, a case study of Uganda Christian University, Mukono - (:unkn) unknown (Uganda Christian University, 2024)
This research study investigated the impact of financial literacy on the long-term financial well-being of students in the university a case study of Uganda Christian University, Mukono. The research study was guided by three objectives that is to say, to analyze the relationship between financial Literacy and long-term financial wellbeing, to identify strategies that can be used to improve students’ financial literacy to enhance their long-term financial wellbeing and to identify the socio demographic factors that influence financial literacy. The study used a cross sectional research design to identify how university student’s long term financial welfare is affected by financial literacy. The targeted population for the study was 2,536 students and a sample of 278 students was selected using stratified sampling technique. Self-administered questionnaires were used for data collection and data was analyzed using SPSS software. The findings were based on a response rate of 73.02%. The study found that; the relationship between financial literacy and long term financial well-being was a moderate positive connection of 0.619 which also indicated the strength between the two of 38%, Potential strategies have been brought up to improve financial literacy among students in the university to enhance their long-term financial health such as workshops, mentorships and inclusion of financial institutions into teaching the students since most students did not consider financial literacy as an important aspect and socio demographic factors such as gender and socio-economic status influence financial literacy of students in the university. Conclusively, financial literacy impacts long term financial wellbeing and the study recommended that policymakers should implement integrating financial literacy among students and young people for a better young generation.